Dandy-Walker Syndrome With Severe Velopharyngeal Dysfunction. Issue 1 (January 2015) - Nelke, Kamil H.; Pawlak, Wojciech; Gerber, Hanna
<x xml:space="preserve">Abstract</x> Abstract Dandy-Walker syndrome is a rare congenital brain deformation. Most symptoms are related with fourth ventricle and skull base malformations. Quite often, symptoms develop from infancy or progress rapidly. Cerebellar dysfunction, lack of muscle coordination, and skull deformities involving eye movement might be present. There are several Dandy-Walker syndrome complex types. We present a 23-year-old patient who had a severe dentofacial deformity with mandibular prognathism and extremely undeveloped maxillary bone resulting in palatopharyngeal and velopharyngeal dysfunction with complete lack of soft palate function resulting in increased speech tone and volume. Performing Le Fort I osteotomy in this case is greatly controversial and might result in even greater loss of function or even its total lack. Velopharyngeal complex is very important, and every surgeon should consider its value while planning Le Fort I osteotomies.